2018
DOI: 10.2139/ssrn.3200136
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Your Boss Make? The Effects of Salary Comparisons

Abstract: Experimental Economics Conference, BEAM, Advances with Field Experiments and the AEA Annual Meetings. The collaborating institution provided financial support for the research being conducted. Additionally, Zoe Cullen was a full-time, salaried employee at that institution while the research was being conducted. This project was reviewed and approved by the Institutional Review Board at University of California Los Angeles (IRB#17-001529).The views expressed herein are those of the authors and do not necessaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(106 reference statements)
1
10
0
Order By: Relevance
“…The slope of this linear relationship (the gray line) corresponds to the coefficient β in the learning equation (3), which measures "spurious" learning. We find significant spurious learning, which is consistent with findings from related studies (see, for example, Fuster et al, 2020;Cullen and Perez-Truglia, 2018). 15 In turn, the red squares correspond to the treatment group (i.e., individuals who receive the inflation feedback).…”
Section: Effect Of Information On Posterior Beliefssupporting
confidence: 89%
See 2 more Smart Citations
“…The slope of this linear relationship (the gray line) corresponds to the coefficient β in the learning equation (3), which measures "spurious" learning. We find significant spurious learning, which is consistent with findings from related studies (see, for example, Fuster et al, 2020;Cullen and Perez-Truglia, 2018). 15 In turn, the red squares correspond to the treatment group (i.e., individuals who receive the inflation feedback).…”
Section: Effect Of Information On Posterior Beliefssupporting
confidence: 89%
“…For instance, the effects of information shocks on inflation expectations last for at least a few months (Cavallo, Cruces, and Perez-Truglia, 2017). 3 Fourth, information experiments similar to the one in this study have been shown to affect high-stakes decisions measured in administrative data: e.g., employees work harder after increasing their expectations of future salary increases (Cullen and Perez-Truglia, 2018), home sellers are less likely to sell their homes when their home price expectations increase (Bottan and Perez-Truglia, 2020b), and employees revise savings decisions in response to feedback about the choices of their peers (Beshears et al, 2015).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…is the wage offer distribution, δ is the exogenous separation rate, and λ is the offer arrival rate; search frictions are captured by lower values of λ . 7 A key assumption of this model is that wages vary across firms but not within firms. The separations (or quits) response to a wage increase, therefore, depends only on market comparisons and is given by dS/dw = −λf (w).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This research explores the non-price interdependencies that intertwine coworkers' fates and finds that typically interdependence limits, rather than heightens, local pay differences. Fairness concerns and workgroup solidarity tend to compress pay inequality (Wilmers, 2019), particularly for horizontal comparisons among peers (Cullen and Perez-Truglia, 2018;Dube, Giuliano, and Leonard, 2018). Similarly, research on team collaboration and peer effects has found that proximity to high-ability peers pulls up workers' productivity, further muting pay differences between coworkers (Mas and Moretti, 2009;Cornelissen, Dustmann, and Schö nberg, 2017).…”
mentioning
confidence: 99%